Diagnosis and treatment of intrauterine adhesions (Bangladesh Journal of Medical Science, 2011)
Intrauterine adhesions develop as a result of intrauterine trauma. The degree of adhesion formation and the impact of the adhesions on the contour of uterine cavity vary greatly. It has been reported that intra abdominal adhesions occur in 60–90% of women who have undergone major gynecological procedures. Hysteroscopy is the gold standard for the diagnosis of severe intrauterine adhesions. Effective methods for preventing adhesions, a variety of surgical techniques and agents have been advocated for the prevention of intrauterine adhesion formation. The present review indicates that there is still no single modality proven to be unequivocally effective in preventing post-operative adhesion formation either for laparoscopic or for hysteroscopic use. Hopefully, the increasing understanding of the future emphasis will probably be on a multimodality therapy, including the use of pharmacologic adjutants in conjunction with a barrier material tailored to the specific operative procedure and a precise surgical technique. Key words: Intrauterine adhesion; hysteroscopy; Pharmacologic adjutants. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7801 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.72-82